2023
DOI: 10.1002/adma.202300947
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Regulation of Protein–Protein Interactions in Artificial Cells

Abstract: Membraneless organelles are important for spatial organization of proteins and regulation of intracellular processes. Proteins can be recruited to these condensates by specific protein–protein or protein–nucleic acid interactions, which are often regulated by post‐translational modifications. However, the mechanisms behind these dynamic, affinity‐based protein recruitment events are not well understood. Here, a coacervate system that incorporates the 14‐3‐3 scaffold protein to study enzymatically regulated rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…1 ). This local concentration represents a 350-fold enhancement of concentration compared to the bulk concentration of 100 nM and is comparable to the 14-3-3 loading that was determined in our previous work 26 . The fluorescein isothiocyanate (FITC)-labeled bivalent c-Raf pS233/pS259 (c-Raf pS) client peptide was added to the separate populations of coacervates at a concentration of 25 nM yielding a 14-3-3/c-Raf pS binding site ratio of 2:1 (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…1 ). This local concentration represents a 350-fold enhancement of concentration compared to the bulk concentration of 100 nM and is comparable to the 14-3-3 loading that was determined in our previous work 26 . The fluorescein isothiocyanate (FITC)-labeled bivalent c-Raf pS233/pS259 (c-Raf pS) client peptide was added to the separate populations of coacervates at a concentration of 25 nM yielding a 14-3-3/c-Raf pS binding site ratio of 2:1 (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Although we have previously used a bioluminescence assay for PPIs in coacervates 26 , confocal microscopy is more suited for determining the localization of a client in a multi-population coacervate sample over time since it additionally provides spatial information and is not enzyme substrate-dependent. Confocal micrographs of the single population coacervates with the different 14-3-3 isoforms showed that, indeed, similar recruitment levels of c-Raf pS were observed after overnight incubation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the incorporation of proteins into synthetic vesicles has attracted massive attention for advanced biological applications, including drug delivery vehicles 21 and artificial cell platforms. 22,23…”
Section: Introductionmentioning
confidence: 99%